Electrochemical Reduction of p-Nitro benzoic acid at Glassy Carbon and Stainless Steel (SS-316) Electrode at Different pH - KUMAR SHARMA, SUSHIL; CHHIMPA, DEVKISHAN; SHARMA, I.K.; VERMA, P.S. (Asian Journal of Chemistry, 2010)
Cyclic voltammogram of p-nitro benzoic acid (aqueous-methanol solution) in BR Buffer at different pH 5 and 9 exhibits the one reduction peak. Effect of scan rate on cathodic peak potential indicates that these reactions are irreversible. Constant current electrolysis in acidic and basic media of p-nitro benzoic acid gives p-amino benzoic acid and 4,4'-dicarboxy azobenzene, respectively. TLC, NMR and IR spectrum analyses confirmed the products.